ANALYSIS OF FACTORS AFFECTING ECONOMIC GROWTH AND SOCIAL DEVELOPMENT OF ROAD AND PORT DEVELOPMENT - Astuti S.T. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Infrastructure development is one of the important, vital and strategic things to accelerate the development process, both nationally, regionally to the regional or village level. In principle, the development of road and port infrastructure has a strategic role in economic growth and regional development, including coastal communities in South Kelumpang District. The purpose of this study is to analyze the factors that influence the economic growth and social development of the construction of roads and ports. This research was conducted with a quantitative approach, with the type of research used was correlation/associative research. The research was conducted from February to April 2021 in South Kelumpang District, Kotabaru Regency, South Kalimantan. The types of data used in this study are primary and secondary data. Primary data were obtained from respondents through interviews and observations related to the construction of roads and ports in South Kelumpang District. Respondents in the study were the people of South Kelumpang District as many as 149 respondents. Data collection methods used in this study include; a) literature study (desk study), b) survey (interview) and c) field observation. The data analysis method used in this research is SEM analysis. The results showed that there are a number of factors that influence economic growth, namely 1) road construction (2,048), 2) port development (2,571) and 3) regional development (2,307). Meanwhile, social development is influenced by 2 factors, namely 1) road construction (4,859) and 2) port development (2,285). In addition, the results of the influence test on regional development factors are also obtained which are influenced by 1) road construction (3.270) and 2) port development (4.104). Meanwhile, community welfare factors are influenced by 1) direct economic growth (4.426), and 2) regional development (4.681).